Elastography Assisted BI‐RADS in the Preoperative Breast Magnetic Resonance Imaging 4a Lesions in China. (10th July 2022) - Tang, Lei; Wang, Yuqun; Gong, Huiling; Chen, Man
Abstract : Objectives: A considerable number of benign lesions, especially category 4a lesions on Breast Imaging Reporting and Data System Magnetic Resonance Imaging (BI‐RADS‐MRI), were biopsied according to BI‐RADS‐MRI, which was a diagnostic imaging challenge. This study aimed to evaluate the diagnostic performance of ultrasound elastography (UE) assisted Breast Imaging Reporting and Data System (BI‐RADS) for BI‐RADS‐MRI category 4a lesions. Methods: Between January 2017 and December 2019, 228 breast lesions categorized as BI‐RADS‐MRI 4a were included. Conventional ultrasound (US) and UE were performed to evaluate each lesion. Pathology results were used as the gold standard. The diagnostic performances of different UE methods and our re‐assessment proposal were evaluated. Results: When BI‐RADS‐MRI category 4a, BI‐RADS‐US category 3‐4a, the stiffness of soft or intermediate in elasticity assessment according to the fifth edition of the BI‐RADS atlas, strain ratio < 1.335, age ≤ 52 years, and the maximum diameter of lesion ≤20 mm were simultaneously met, an ultrasound‐guided empty needle biopsy was not recommended, but short‐term ultrasound follow‐up for 3–6 months was recommended, and biopsy was performed after changes in evaluation. In this way, 95 of 228 BI‐RADS‐MRI category 4a lesions avoided biopsies, and the number of patients with biopsies decreased by 41.7%. Conclusions: UE offers benefits in the characterization of BI‐RADS‐MRI category 4a lesions. Ultrasound and elastography can help optimize therapy recommendations for BI‐RADS‐MRI category 4a lesions by our re‐assessment proposal.